2008
DOI: 10.1681/asn.2007040469
|View full text |Cite
|
Sign up to set email alerts
|

The Local and Systemic Inflammatory Transcriptome after Acute Kidney Injury

Abstract: Studies in humans and animal models have demonstrated that acute kidney injury (AKI) has a significant effect on the function of extrarenal organs. The combination of AKI and lung dysfunction is associated with 80% mortality; the lung, because of its extensive capillary network, is a prime target for AKI-induced effects. The study presented here tested the hypothesis that AKI leads to a vigorous inflammatory response and produces distinct genomic signatures in the kidney and lung. In a murine model of ischemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
218
0
9

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(237 citation statements)
references
References 50 publications
10
218
0
9
Order By: Relevance
“…[12][13][14][15] These adverse effects may partially contribute to the poor long-term survival observed in patients who have AKI and eventually recover renal function. 16,17 Similar to AKI, DGF in KTR is associated with the modulation of leukocyte/endothelial function, upregulation of cytokines/adhesion molecules, and increase in markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] These adverse effects may partially contribute to the poor long-term survival observed in patients who have AKI and eventually recover renal function. 16,17 Similar to AKI, DGF in KTR is associated with the modulation of leukocyte/endothelial function, upregulation of cytokines/adhesion molecules, and increase in markers of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…21 Several pro-inflammatory cytokines contribute to the development of sepsis, and others may be identifiable from other kinds of genetic screens. 22 For instance, administration of recombinant IL-1 or TNF-␣ induces many of the features observed after lipopolysaccharide exposure or sepsis itself. 18,19 Furthermore, anti-TNF monoclonal antibodies have beneficial effects in several animal models of sepsis.…”
mentioning
confidence: 99%
“…More specifically, as far as open AAA repair and NGAL level changes are concerned, an increase in serum NGAL (75.21±55.83 vs. 46.37±21.60 ng/ml, p>0.05) and significantly elevated plasma NGAL levels at 2 h (91.54±76.54 vs. baseline, p<0.05), 12 h (100.78±44.92 vs. baseline, p<0.05), and 24 h (89.46±94.18 vs. baseline, p<0.05) after clamp release and reperfusion were found [33,34].…”
Section: Ngal and Aaa Natural Historymentioning
confidence: 88%
“…In cases of open AAA repair, it is shown that after clamp removal, NGAL washes out from the lower extremities, which become ischemic during aneurysm repair [33]. Additionally, AAA surgery triggers an inflammatory reaction and thus the increase of NGAL, which is known to be an acute-phase reactant produced by some immune cells [33].…”
Section: Ngal and Aaa Natural Historymentioning
confidence: 99%
See 1 more Smart Citation